Clinical implication of serum Wisteria floribunda agglutinin positive Mac-2-binding protein level on hepatitis B e-antigen loss or seroconversion in hepatitis B e-antigen positive patients - Nishikawa, Hiroki; Enomoto, Hirayuki; Iwata, Yoshinori; Kishino, Kyohei; Shimono, Yoshihiro; Hasegawa, Kunihiro; Nakano, Chikage; Takata, Ryo; Nishimura, Takashi; Yoh, Kazunori; Ishii, Akiio; Aizawa, Nobuhiro; et al. (Hepatology research, 2016)
Aim: To examine the impact of pretreatment Wisteria floribunda agglutinin positive Mac‐2‐binding protein (WFA+‐M2BP) level on hepatitis B e‐antigen (HBeAg) loss or HBeAg seroconversion (SC) for patients with nucleoside/nucleotide analog (NUC) therapy naive HBeAg positive chronic hepatitis B (CHB). Methods A total of 57 patients were analyzed. All subjects were initially treated with NUC. We examined the impact of pretreatment WFA+‐M2BP level on HBeAg loss and HBeAg SC using univariate and multivariate analyses. Results There were 36 men and 21 women (median age, 39 years). The WFA+‐M2BP cut‐off index (COI) level ranged 0.43–12.9 (median, 1.55). WFA+‐M2BP level in patients with F3 or F4 was significantly higher than that with F0–F2. WFA+‐M2BP level in patients with A2 or 3 was significantly higher than that with A0 or 1. For all cases, the 1‐ and 3‐year cumulative HBeAg loss rates were 10.5% and 34.4% and the corresponding cumulative HBeAg SC rates were 8.8% and 29.0%, respectively. In the multivariate analysis, in terms of HBeAg loss, pretreatment HBV DNA of 5 log copies/mL or more and pretreatment WFA+‐M2BP level of more than 1.55 COI tended to be significant factors linked to loss of HBeAg, while in terms of HBeAg SC, pretreatment HBV DNA of 5 log copies/mL or more was an independent predictor and pretreatment WFA+‐M2BP level of more than 1.55 COI tended to be a significant factor. Conclusion Pretreatment WFA+‐M2BP level may be a useful predictor for HBeAg loss or SC after NUC therapy for patients with HBeAg positive CHB.